Construction of Chicken Drinking Water Sterilization Device Using Ultraviolet Light Based on ATMega8535 Microcontroller - Perangin-Angin, Bisman (Journal of Technomaterial Physics, 2021)
This research aimed to design of a chicken drinking water sterilization device using ultraviolet light-based microcontroller ATMega8535. After constructing the device, the test that is carried out were running the system according to the procedure, observing the performance of the system that begins with setting the sterilization timer at the minimum position, and recording the results. After the power supply was activated, the potentiometer of timer set to a minimum. The pump was on for 1 minute, then the UV lamp was also active and the process continues to repeat. Potentiometer was set to increase by 50% timer in 5 minutes position, and raised again to 100% at 10 minute position. The control process of this system is carried out by an ATMega8535 microcontroller that regulates the process of draining water from the container to the pipe, the length of time it takes to activate the ultraviolet lamp and the length of time it takes to activate the pump. This device was designed to demolish germs and bacteria in the water. The test resulted in a 100% reduction in bacteria in ultraviolet-illuminated water.